1996
DOI: 10.1021/jf950542d
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Benoxacor Metabolism and Identification of Benoxacor Metabolites Isolated from Suspension-Cultured Zea mays Cells 1 h after Treatment

Abstract: Extracts of suspension-cultured Zea mays (cv. Black Mexican Sweet) cells treated with [14C]benoxacor for 0.25−24 h were analyzed by HPLC and TLC to investigate the metabolic fate of benoxacor. Thin layer chromatography determined that benoxacor was rapidly metabolized to six detectable metabolites within 0.5 h. Twelve metabolites were detected in extracts from cells treated for 24 h. Analysis of cell extracts by reversed phase HPLC determined that the glutathione conjugate [mono(GSH)] of benoxacor was present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 20 publications
0
37
1
Order By: Relevance
“…Using these reference benoxacor metabolites, extracts from the suspension cultures treated with the safener for 16 h were then analysed by HPLC-ESI-MS. No parent benoxacor was identified, demon- strating that the safener had been metabolised. While the glutathionylated conjugates of the safener could not be detected, the formylcarboxyamide metabolite which is formed as a consequence of S-glutathionylation (Miller et al, 1996b), was observed in benoxacor-treated cultures but not in the controls. This confirmed that benoxacor was being rapidly conjugated with glutathione in Arabidopsis as demonstrated in maize cell cultures (Miller et al, 1996a,b).…”
Section: Safening Of Arabidopsis Cell Cultures By Benoxacormentioning
confidence: 80%
See 2 more Smart Citations
“…Using these reference benoxacor metabolites, extracts from the suspension cultures treated with the safener for 16 h were then analysed by HPLC-ESI-MS. No parent benoxacor was identified, demon- strating that the safener had been metabolised. While the glutathionylated conjugates of the safener could not be detected, the formylcarboxyamide metabolite which is formed as a consequence of S-glutathionylation (Miller et al, 1996b), was observed in benoxacor-treated cultures but not in the controls. This confirmed that benoxacor was being rapidly conjugated with glutathione in Arabidopsis as demonstrated in maize cell cultures (Miller et al, 1996a,b).…”
Section: Safening Of Arabidopsis Cell Cultures By Benoxacormentioning
confidence: 80%
“…Using the published data from these metabolism studies, reference benoxacor metabolites were synthesised and characterised by HPLC-MS. The most abundant products derived from this chemical conjugation (Miller et al, 1996b) . Using these reference benoxacor metabolites, extracts from the suspension cultures treated with the safener for 16 h were then analysed by HPLC-ESI-MS. No parent benoxacor was identified, demon- strating that the safener had been metabolised.…”
Section: Safening Of Arabidopsis Cell Cultures By Benoxacormentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic standards of the glutathione and cysteine conjugates of [ 14 C]dimethenamid (synthesis protocol described below) and parent [ 14 C]dimethenamid were spotted for reference. The plate was developed twice in the same dimension using a chloroform/methanol/formic acid/water solvent system (first 75: 25:4:2 and then 60:40:4:2 v/v/v/v) (Miller et al, 1996). The solvent front was allowed to migrate to the top of the plate during each run (20 cm).…”
Section: Chemicalsmentioning
confidence: 99%
“…To date, such multiple rounds of conjugation of xenobiotics have rarely been recorded. A notable example is the safener benoxacor, which undergoes two rounds of glutathionylation in maize suspension cultures (30,31).…”
Section: Discussionmentioning
confidence: 99%